Cistercian Pavements from Santa Maria de Alcobaça Abbey: first examples of tin-glazed tiles in Portugal - Carvalho, Fernanda (2016)
The Mosteiro de Alcobaça (Alcobaça Monastery, founded in 1153) was built to the image of Clairvaux Abbey, founded by the Cistercian abbot St. Bernard. In many ways Alcobaça mirrored the original concepts of the Cistercian Order, with an austere architectural style and shedding signs of richness. The glazed tiles found on the pavement of the deambulatory and some adjacent chapels are some of the first examples of lead-tin glazes in Christian Portugal. For the first time, these tiles were analytically characterized, to determine their chemical composition, production technology and decoration technique. The analytical techniques used were μ-PIXE (particle-induced X-ray emission), SEM-EDS (scanning electron microscopy with energy-dispersive X-ray spectrometry), and μ-Raman spectroscopy.